OpenStudy (anonymous):

Let f(x) = -4x + 7 and g(x) = 10x - 6, find f(g(x)).

3 years ago
OpenStudy (jdoe0001):

\(\bf f(x) = -4x + 7\qquad {\color{red}{ g(x)}} = 10x \\ \quad \\ f(\quad g(x)\quad )=-4({\color{red}{ 10x}}) + 7\)

3 years ago
OpenStudy (mathmale):

Kidd: f(g(x)) is called a "composite function." g(x) becomes the input to the other function, f(x). Note how JDoe has replaced x within f(x) with g(x), on the left, and then replaced x with 10x, on the right. Just simplify the expression on the right and you'll have the appropriate expression for f(g(x)).

3 years ago